2009
DOI: 10.4321/s1130-01082009001000002
|View full text |Cite
|
Sign up to set email alerts
|

Viral kinetics during the first month of treatment in patients with genotype 1 chronic hepatitis C

Abstract: Objective: to identify predictive factors of response to pegylated interferon alpha-2b and ribavirin in patients with genotype 1 chronic hepatitis C. Viral kinetics were studied in weeks 2 and 4.Methods: a prospective and consecutive study of patients with genotype 1 chronic hepatitis C referred to our Hepatology Clinic between January 2004 and October 2006 for antiviral treatment. Baseline data were recorded and viremia levels were determined hours before the weekly dose of pegylated interferon by qualitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
2
4
0
1
Order By: Relevance
“…Age directly correlates with the duration of the infection, although in many cases the date and mechanism of infection are unknown, a fact that justifies the relatively poor statistical power of this factor. We also confirmed previous reports signaling that a low viral load is the strongest predictor of SVR when the comparison is made with patients who suffer primary failure; unfortunately, only a minority of genotype 1 patients are included in this category (17,19,20,22,23). We used the limit of 400,000 IU/mL proposed by Witthöft et al (5) as the best discriminant one between low and high viral rate, but results would not have changed if higher limits (600,000 or 800,000 IU/mL) had been used instead.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Age directly correlates with the duration of the infection, although in many cases the date and mechanism of infection are unknown, a fact that justifies the relatively poor statistical power of this factor. We also confirmed previous reports signaling that a low viral load is the strongest predictor of SVR when the comparison is made with patients who suffer primary failure; unfortunately, only a minority of genotype 1 patients are included in this category (17,19,20,22,23). We used the limit of 400,000 IU/mL proposed by Witthöft et al (5) as the best discriminant one between low and high viral rate, but results would not have changed if higher limits (600,000 or 800,000 IU/mL) had been used instead.…”
Section: Discussionsupporting
confidence: 90%
“…Together with a high viral load, GGT and plasma cholesterol levels were the factors most strongly associated to the risk of primary failure in our study. GGT has been identified as a prognostic factor in other studies (17,23) and it is also a surrogate marker of liver fibrosis, as corroborates its inclusion in non-invasive scoring systems aimed to evaluate the stage of fibrosis (25). Moreover, GGT levels are related with an increased expression of TNFα in the liver that seems to reduce the efficacy of antiviral therapy (26).…”
Section: Discussionmentioning
confidence: 61%
“…These results are in agreement with other reports as in all large prospective studies of (PEG) IFN and RBV combination therapy younger age correlated significantly with an SVR when assessed by univariate and multivariate analyses and patients younger than 40-45 years showed the best response rates [50] . GGT has been identified as a prognostic factor in other studies [51,52] . In this study, we found that low GGT level had a favorable prediction of SVR.…”
Section: Discussionmentioning
confidence: 93%
“…En el presente número de la Revista Española de Enfermedades Digestivas, Hernández y cols. (20) se ocupan de este aspecto buscando la relación entre la cuantía del descenso de la carga viral antes del primer mes de tratamiento y la posibilidad de previsión de la respuesta al final de mismo, encontrando alto valor predictivo para la ya conocida respuesta rápida y, también, para descensos de 2 log 10 a las 2 y 4 semanas, a pesar de que la serie es relativamente corta. Esta intensidad del decremento de viremia supone adelantar el concepto de respuesta precoz a las semanas 2 y 4, y es lógico que si la respuesta esperada a los 3 meses se produce mucho antes identifique a los que finalmente erradiquen la infección (siempre confiando en que completarán el tratamiento), aunque el valor predictivo negativo tenga que ser necesariamente menor, ya que pacientes con descensos de la carga viral inferiores a esa cifra pueden alcanzar con posterioridad respuesta precoz y terminar con respuesta sostenida.…”
Section: Editorialunclassified
“…Several studies suggest that decreases in viral load will be identified in association with potential sustained responses in much less than 4 weeks, maybe during the first few days on therapy (17)(18)(19). In the current issue of Revista Española de Enfermedades Digestivas, Hernández et al (20) deal with this issue by researching the relationship between viral load decrease within one month after treatment onset and the possibility of predicting response at therapy completion; they find a high predictive value for rapid response, and also for reductions by 2 log 10 at 2 and 4 weeks, despite the series' limited size. This amount of viral load reduction leads to consider rapid response at weeks 2 and 4, and if the expected response at 3 months ultimately occurs much earlier this will logically identify those who will eventually have their infection eradicated (provided they will complete therapy), even though the negative predictive value becomes necessarily lower, since patients with smaller viral load decreases may later present with early response and then exhibit sustained response.…”
mentioning
confidence: 99%